(untitled) (Global Journal of Human-Social Science, 2018)
This study investigated the use of reader engagement in 60 RAs from the international linguistic journal Language Learning Based on the Model of Stance and Engagement and IMRD Structure under Genre Analysis theory findings suggested that there appear a total of 53 1 reader engagement markers per 10 000 words Under IMRD Structure reader engagement markers occur most frequently in Introduction section 76 9 words per 10 000 words followed by Discussion Method and Results There exists a significant difference of the distribution in reader engagement markers among the four sections X2 22 747 df 3 p 001 Under the Model of Stance and Engagement the frequency of Directives category 102 8 times per 10 000 words is highest followed by Appeals to Shared Knowledge Personal Asides Reader Mentions and Questions The distributions of five engagement markers are significantly different within each section X2 109 466 df 4 p 001 X2 268 079 df 3 p 001 X2 234 765 df 4 p 001 X2 600 722 df 4 p 001 A significant difference is found in the overall distribution of five engagement markers among the four sections X2 102 552 df 4 p 001 Meanwhile this study offers suggestions for the teaching of reader engagement in academic writing